2012
DOI: 10.1021/mp300194b
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Individual Carbohydrate-Binding Sites in the Function of the Potent Anti-HIV Lectin Griffithsin

Abstract: Griffithsin (GRFT) is a lectin that has been shown to inhibit HIV infection by binding to high mannose glycan structures on the surface of gp120, and it is among the most potent HIV entry inhibitors reported so far. However, important biochemical details on the antiviral mechanism of GRFT action remain unexplored. In order to understand the role of the three individual carbohydrate-binding sites (CBS) in GRFT, mutations were made at each site (D30A, D70A, and D112A), and the resulting mutants were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 66 publications
3
69
0
Order By: Relevance
“…These include Asp30, Asp70 and Asp112 that make hydrogen bonding interactions with O5 and O6 of mannose [15] (Figure 1C). Mutations of these residues to Ala do not affect the folding of the protein but weaken the binding to a mannose column [18]. …”
Section: Three-dimensional Structurementioning
confidence: 99%
“…These include Asp30, Asp70 and Asp112 that make hydrogen bonding interactions with O5 and O6 of mannose [15] (Figure 1C). Mutations of these residues to Ala do not affect the folding of the protein but weaken the binding to a mannose column [18]. …”
Section: Three-dimensional Structurementioning
confidence: 99%
“…As a model for interrogating multivalent oligomannose interactions we used the mannose-binding lectin griffithsin (GRFT), a homodimeric protein that contains three mannose-binding sites per subunit. [6] The triangular arrangement of these binding sites facilitates multivalent interactions.…”
mentioning
confidence: 99%
“…[6c] Changes in the signal intensities relative to unbound GRFT were plotted as a function of amino acid residue (see the Supporting Information). [6c] Data for three glycopep-tides that show either strong affinity for GRFT by ITC or very slow k off rates by SPR are presented in Figure 3. For high-affinity glyco-peptide Om 3 G 0 ( 7 ), changes in cross-peak intensity are observed only for residues located in the mannose-binding pockets (Figure 3A).…”
mentioning
confidence: 99%
“…Note : The resulting GRFT will contain two extra glycine residues at the N-terminus. NMR and functional studies have shown these to not interfere with the activity of GRFT (Lusvarghi, Ghirlando, Wong, & Bewley, 2015; Xue et al, 2012). …”
Section: Selection and Production Of The Lectinmentioning
confidence: 99%